2019
DOI: 10.1002/1878-0261.12444
|View full text |Cite
|
Sign up to set email alerts
|

Obesity‐induced MBD2_v2 expression promotes tumor‐initiating triple‐negative breast cancer stem cells

Abstract: Obesity is a risk factor for triple‐negative breast cancer ( TNBC ) incidence and poor outcomes, but the underlying molecular biology remains unknown. We previously identified in TNBC cell cultures that expression of epigenetic reader methyl‐CpG‐binding domain protein 2 ( MBD 2), specifically the alternative mRNA splicing variant MBD variant 2 ( MBD 2_v2), is dependent on reactive oxygen species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 77 publications
5
43
0
Order By: Relevance
“…Furthermore, TNFα upregulates TAZ (a Hippo pathway effector) and Slug (an EMT mediator), which increase breast CSCs through both canonical and non-canonical NF-κB signaling [ 117 , 118 ]. Analysis of TNBC patient datasets reveals high tumor expression of the epigenetic reader methyl-CpG-binding domain protein 2 (MBD2), specifically the alternative splicing variant 2 (MBD2_v2) expression and high relapse rate and high BMI [ 119 ]. It is postulated that obesity drives high reactive oxygen species (ROS) levels, which subsequently promotes MBD2_v2 expression and an expansion of the CSC fraction [ 119 ].…”
Section: Mechanisms Linking Adipose Tissue To the Metastatic Cascamentioning
confidence: 99%
“…Furthermore, TNFα upregulates TAZ (a Hippo pathway effector) and Slug (an EMT mediator), which increase breast CSCs through both canonical and non-canonical NF-κB signaling [ 117 , 118 ]. Analysis of TNBC patient datasets reveals high tumor expression of the epigenetic reader methyl-CpG-binding domain protein 2 (MBD2), specifically the alternative splicing variant 2 (MBD2_v2) expression and high relapse rate and high BMI [ 119 ]. It is postulated that obesity drives high reactive oxygen species (ROS) levels, which subsequently promotes MBD2_v2 expression and an expansion of the CSC fraction [ 119 ].…”
Section: Mechanisms Linking Adipose Tissue To the Metastatic Cascamentioning
confidence: 99%
“…Aberrant DNA methylation modifications are frequently detected in various tumors, and the main mechanisms for DNA methylation-involved tumorigenesis are that methylation levels of the promoter region of anti-oncogene are elevated, which promotes the key anti-oncogene silencing and drives tumorigenesis. 12,[14][15][16] MBD2 has been reported in multiple human malignancies, including gastric cancer, 17 breast cancer, 18,19 colorectal cancer, 20 glioblastoma, 21,22 hilar cholangiocarcinoma, 23 hepatocellular carcinoma, 24,25 chronic myeloid leukemia 26 and prostate cancer. 27 Previous studies confirmed that MBD2 mediates the transcriptional repression of tumor suppressor genes, such as hTERT, 28 GSTP1, 29 BAI1, 21 p14 ARF /p16 INK4a,30 and 14-3-3sigma, 27 which supports the pivotal role of MBD2 in abnormal epigenetic regulation of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…TET1 expression was demonstrated to promote cell metastasis in colorectal cancer and activation of PI3K oncogenic signaling in TNBC. TET1 expression was shown to correlate with cell migration, cancer stemness tumorigenicity, and poor survivals in epithelial ovarian cancer and in TNBCs [ 77 , 78 , 79 ].…”
Section: Are Tet Enzymes Tumor-suppressors or Oncogenes?mentioning
confidence: 99%